Epidemiological Aspects of Chikungunya in The State of Espírito Santo, Brazil, 2014 A 2017 - Cardoso Silva, Theresa Cristina; Brioschi dos Santos, Ana Paula; Moussallem, Moussallem; da Penha Valadares Koski, Aline; Rocha Araujo Nader, Priscilla (Guará Journal, 2018)
In order to describe the temporal and spatial distribution of Chikun-gunya in Espírito Santo, it was made an observational study between 2014 and 2017. We analyzed the notifications in SINAN and organized it at the Excel program. Then, the data were analyzed by SPSS and Arc-GIS software to construct the maps. A progressive rise in the numbers of cases was registered since 2015, and the incidence in 2017 (12,8/100.000 habitants) doubled in relation to 2016 (6,3/100.000 habitants). From the confirmed patients, 392 (66,9%) were women and 194 (33,1%) were men. The brown-skinned people and those between 41-60 year-old were the most affected and 15% of the population had high-school level of ed-ucation. The most common signs and symptoms were: fever (85,5%), arthralgias (79,7%), myalgias (78,3%), headache (67,4%). Approximately 16,4% of the population informed any comorbidity. 288 cases (49,1%) were confirmed by laboratory. The epidemic profile of Chikungunya, with high morbidity rates, associated to persistent arthralgias, resulting in productivity reduction and quality of life, suggest the urgent need of better organization of the health services to face the disease and pro-vide an appropriate and multiprofessional service in public health departments